2020
DOI: 10.1186/s13098-020-00526-2
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and metabolic syndrome components among older Chinese adults

Abstract: Background: Few studies examined associations between depressive symptoms and metabolic syndrome (MetS) among older Chinese adults. Considering that the prevalence of depressive symptoms is high in older Chinese adults, we aimed to examine associations of depressive symptoms with MetS and its components in older Chinese adults.Methods: Data from a community-based cross-sectional study of 4579 Chinese adults aged 60 years or older were analyzed. Depressive symptoms were assessed using the nine-item Patient Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
2
6
0
1
Order By: Relevance
“…Распространенность данной патологии увеличивается при старении у лиц обоих полов. В то же время, несмотря на то, что симптомы депрессии, наблюдаемые в пожилом возрасте, были связаны с компонентами МС (повышенным уровнем глюкозы в плазме натощак и диабетом), эта связь была менее выражена у женщин [30]. Нарушения сна также характерны для лиц старшей возрастной группы.…”
Section: факторы обусловливающие распространенность метаболического синдромаunclassified
“…Распространенность данной патологии увеличивается при старении у лиц обоих полов. В то же время, несмотря на то, что симптомы депрессии, наблюдаемые в пожилом возрасте, были связаны с компонентами МС (повышенным уровнем глюкозы в плазме натощак и диабетом), эта связь была менее выражена у женщин [30]. Нарушения сна также характерны для лиц старшей возрастной группы.…”
Section: факторы обусловливающие распространенность метаболического синдромаunclassified
“…The Weitang Geriatric Diseases Study is a communitybased study conducted in Weitang town located in Suzhou of China from August 2014 to January 2015. The detailed study protocol and some other findings have been reported in previous reports (7,8,9,10,11). In brief, invitation letters were sent to 6030 residents aged 60 years or older in the Weitang town based on official records.…”
Section: Study Populationmentioning
confidence: 99%
“…Details of the baseline study have been described elsewhere. [15][16][17] In the baseline examinations, 6030 families who had an older adult aged 60 years or older based on local official records received an invitation letter, which explained the nature of the study and invited the older adults to participate. Exclusion criteria applied to those who had been living there shorter than six months, had migrated from the residing address, or had deceased.…”
Section: Study Design and Proceduresmentioning
confidence: 99%